Students’ Perception and Motivation toward English E-Learning during Covid-19 Pandemic of Eleventh Grade Students at SMAN 1 Monta - Irawati, Ika; Ningsi, Fitri; Nurhidayat, Nurhidayat (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2022)
This research aimed at knowing the students' perception towards English E-Learning during Covid-19 pandemic at SMA N 1 Monta. This research generally answered two questions as follows: (1) What are students’ perceptions towards English E-Learning during Covid-19 pandemic? (2) How are students’ motivation towards English E-Learning during Covid-19 pandemic? The data was collected through a questionnaire and interviews. There were 31 students of MIPA-2 in eleventh graders at SMA N 1 Monta participated in this research. Since this research explored the students' perception and motivation which coming from the students' experiences during Covid-19 pandemic, descriptive research by using qualitative techniques was considered as an appropriate approach as a type of research. The result of this research was presented descriptively in order to reveal the students' perception and motivation comprehensively. The researcher found E- learning gets positive perception because it is flexible and effective. Meanwhile, its flexibility makes some students motivated but some are being lazy in doing it and choose to procrastinate the assignments.